2021
DOI: 10.1101/2021.02.05.429932
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Integrity of the Speciation Core Complex is necessary for centromeric binding and reproductive isolation inDrosophila

Abstract: Postzygotic isolation by genomic conflict is a major cause for the formation of species. Despite its importance, the molecular mechanisms that result in the lethality of interspecies hybrids are still largely unclear. The genus Drosophila, which contains over 1600 different species, is one of the best characterized model systems to study these questions. We showed in the past that the expression levels of the two hybrid incompatibility factors Hmr and Lhr diverged in the two closely related Drosophila species,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…S3B, E). Similarly, the D1-interacting heterochromatin protein, Hmr, which contributes to TE repression, was also observed at the chromocenter boundary, in agreement with recent reports suggesting that Hmr may bridge centromeric and pericentromeric heterochromatin [24,27] (Fig. S3C, F).…”
Section: Te Repression Proteins Are Associated With Chromocenterssupporting
confidence: 91%
See 1 more Smart Citation
“…S3B, E). Similarly, the D1-interacting heterochromatin protein, Hmr, which contributes to TE repression, was also observed at the chromocenter boundary, in agreement with recent reports suggesting that Hmr may bridge centromeric and pericentromeric heterochromatin [24,27] (Fig. S3C, F).…”
Section: Te Repression Proteins Are Associated With Chromocenterssupporting
confidence: 91%
“…The copyright holder for this preprint this version posted July 12, 2023. ; https://doi.org/10.1101/2023.07.11.548599 doi: bioRxiv preprint proteins [23][24][25] or centromeric proteins [24,26,27]. In addition, these studies have largely been performed in cultured cells and we still lack detailed knowledge of the heterochromatin-associated proteome in intact tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work from other groups have shown that Hmr and Lhr can localize to chromocenters ( Brideau et al 2006 ; Satyaki et al 2014 ; Kochanova et al 2020 ) and exhibit increased expression levels in lethal male hybrids ( Thomae et al 2013 ). Moreover, Hmr and Lhr colocalize/form complexes with Gfzf in both pure species and hybrids ( Cooper et al 2019 ; Lukacs et al 2021 ). We therefore speculate that a complex of HI factors in hybrids could inhibit either the protein–DNA or protein–protein interactions that contribute to chromocenter formation ( fig.…”
Section: Chromocenter Disruption Is a Common Phenotype Among Drosophila Hybridsmentioning
confidence: 99%